Land Usage and Siida Autonomy - Sara, Mikkel Nils (Arctic Review on Law and Politics, 2011)
The 2007 Reindeer Husbandry Act acknowledged in principle the tra- ditional Sámi siida as a rights holder and basic unit of the working partnership. The Act provides a definition of the siida and certain provisions concerning its institutional aspects. The siida system had lost prominence under the Reindeer Herding District regime. Two basic issues must now be determined to restore siida autonomy – animal numbers, and siida rules of land usage. The article dis- cusses these issues in relation to traditional reindeer herding customs.Keywords: Sámi, siida, reindeer husbandry, land, scientific and juridical approach, herding concepts.Citation: Arctic Review on Law and Politics, vol. 3, 2/2011 p. 138–158. ISSN 1891-6252